Pengaruh Pendapatan, Jumlah Anggota Keluarga, dan Pendidikan Terhadap Pola Konsumsi Rumah Tangga Miskin di Kecamatan Gianyar - Erwin, Pande Putu; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2012)
The purpose of this study was to obtain empirical evidence that income, number of family members, and education affected by simultaneous consumption patterns of poor households in the district of Gianyar. This study uses primary data. This study population is poor households in the district of Gianyar. This sample selection method is by using Slovin. Data were analyzed use the regression analysis. The results indicate that income, family size, and education affect consumption patterns.
Keywords: income; family number; education; consumption pattern